Review of the Influence of Women's Empowerment on Maternal Health Outcomes - Pramesty, Regitha Adit; Sonawati, Sonawati; Adnani, Qorinah Estiningtyas Sakilah; Susiarno, Hadi (Master Program of Health Promotion Faculty of Public Health Diponegoro University, 2025)
Background: Many studies have examined the impact of empowerment on maternal health outcomes, yet few have addressed the specific contexts through which empowerment influences health outcomes. This study aimed to explore the contexts in which empowerment affects maternal health status.Method: This literature review used studies from PubMed and Semantic Scholar databases. Articles were included if published within the last five years and provided free full-text access. Exclusion criteria included studies deemed irrelevant. All included articles were thoroughly reviewed. A total of 13 articles were identified and reviewed.Result: The findings revealed that women's empowerment influences maternal health through various pathways. Financial empowerment, including control over household expenditures and access to income, along with social empowerment—characterized by mobility, decision-making autonomy, access to communication tools, and rejection of spousal violence—was associated with increased antenatal care (ANC) visits, greater utilization of skilled birth attendants (SBAs), and a higher likelihood of delivering in healthcare facilities. In turn, it impacts maternal health status, as they are associated with reduced risk of complications. Furthermore, cultural and structural barriers, such as patriarchal norms and gender-based restrictions, were identified as challenges to empowerment.